Pengaruh Kualitas Pelayanan Terhadap Loyalitas Muzakki Melalui Kepuasan Muzakki Sebagai Variabel Intervening Pada Badan Amil Zakat Nasional (BAZNAS) Kota Serang - Syihabudin Said; Tenny Badina; Syarah Syahidah (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2020)
This study aims to determine (1) the quality of service does not directly affect the loyalty of muzakki; (2) the quality of service had a significant effect on muzakki satisfaction; (3) muzakki satisfaction has a direct effect on muzakki loyalty; (4) muzakki satisfaction is able to mediate the quality of service and muzakki loyalty. This study uses a quantitative approach. The population in this study were all muzakki of  BAZNAS Serang City. The sampling technique used in this study was purposive sampling obtained by 65 muzakki. The results showed that: (1) the quality of service does not directly affect the loyalty of muzakki, as evidenced by the significance value of 0,140 > 0,05 and the regression coefficient of 0,134; (2) the quality of service had a significant effect on muzakki satisfaction, evidenced by a significance value of 0,000 < 0,05 and a regression coefficient of 0,530; (3) muzakki satisfaction has a direct effect on muzakki loyalty, as evidenced by the significance value of 0,000 < 0,05 and a regression coefficient of 0,721; (4) muzakki satisfaction is able to mediate the quality of service and muzakki loyalty.